Inovasi Makanan Tradisional Lomang Sebagai Proyek Penguatan Profil Pelajar Pancasila (P5) Pada SMPN 6 Kuantan Mudik - Susda Heleni; Aditia Eka Putra; Feby Khairani; Erni Yunita Napitupulu; Naomi Evelyn Tamariska Sinaga; Theresia Octavia Sinaga; Marshelli; Meisye Wulandari; Muhammad Resha Alijati; Thifal Joitsa (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2022)
Lomang is a type of traditional Indonesia food made from glutinous rice wrapped in banana leaves and put in a bamboocontainer. The food processing is stillvery traditional using a stove that is specially designed to be burned. During the burning process, the position of the bamboo must be contiuously changed so that the sticky rice inside is cooked evenly. Luai village uses lomang as a source of side business and is usually sold to various places such as markets. Lomang sold is also very varied, renging from sweet potato lomang, sticky rice lomang, durian lomang, and sarikaya lomang. The implementation of the Riau University KUKERTA activity in Luai village took part in the process of making lomang together with the students and the teacher assembely of SMPN 6 Kuantan Mudik. The results of the lomang will be exhibited at the opening bazaar of the Cultural Track Festival.